Synergy and competition during the anaerobic degradation of N-acetylglucosamine in a methane-emitting, subarctic, pH-neutral fen - Kujala, Katharina; Schmidt, Oliver; Horn, Marcus A. (Frontiers in Microbiology, 2024)
Peatlands are invaluable but threatened ecosystems that store huge amounts of organic carbon globally and emit the greenhouse gasses carbon dioxide (CO2) and methane (CH4). Trophic interactions of microbial groups essential for methanogenesis are poorly understood in such systems, despite their importance. Thus, the present study aimed at unraveling trophic interactions between fermenters and methanogens in a nitrogen-limited, subarctic, pH-neutral fen. In situ CH4 emission measurements indicated that the fen is a source of CH4, and that CH4 emissions were higher in plots supplemented with ammonium compared to unsupplemented plots. The amino sugar N-acetylglucosamine was chosen as model substrate for peat fermenters since it can serve as organic carbon and nitrogen source and is a monomer of chitin and peptidoglycan, two abundant biopolymers in the fen. Supplemental N-acetylglucosamine was fermented to acetate, ethanol, formate, and CO2 during the initial incubation of anoxic peat soil microcosms without preincubation. Subsequently, ethanol and formate were converted to acetate and CH4. When methanogenesis was inhibited by bromoethanesulfonate, acetate and propionate accumulated. Long-term preincubation considerably increased CH4 production in unsupplemented microcosms and microcosms supplemented with methanogenic substrates. Supplemental H2-CO2 and formate stimulated methanogenesis the most, whereas acetate had an intermediary and methanol a minor stimulatory effect on methane production in preincubated microcosms. Activity of acetogens was suggested by net acetate production in microcosms supplemented with H2-CO2, formate, and methanol. Microbial community analysis of field fresh soil indicated the presence of many physiologically unresolved bacterial taxa, but also known primary and secondary fermenters, acetogens, iron reducers, sulfate reducers, and hydrogenotrophic methanogens (predominately Methanocellaceae and Methanoregulaceae). Aceticlastic methanogens were either not abundant (Methanosarcinaceae) or could not be detected due to limited coverage of the used primers (Methanotrichaceae). The collective results indicate a complex interplay of synergy and competition between fermenters, methanogens, acetogens, and potentially iron as well as sulfate reducers. While acetate derived from fermentation or acetogenesis in this pH-neutral fen likely plays a crucial role as carbon source for the predominant hydrogenotrophic methanogens, it remains to be resolved whether acetate is also converted to CH4 via aceticlastic methanogenesis and/or syntrophic acetate oxidation coupled to hydrogenotrophic methanogenesis.